A Bibliography of publications in economic and social history printed in Poland in 1994-1995 - Kowal, Ewelina (Studia Historiae Oeconomicae, 2001)
With the supplements for the years 1992-93. I. Bibliography 191 II. Methodology, theory and history of economic thought 192 III. Sources and source studies 193 IV. General publications 196 V. Demography 198 VI. Social structure and mobility 200 VII. Labour, social movements and trade unions 204 VIII. Social and economic relations in rural communities 204 IX. Towns and urbanization processes 205 X. Industry, mining, handicraft and architecture 208 XI. Transport and communication 210 XII. Maritime economy, aquatic economy 210 XIII. Trade 211 XIV. Credit, finance, money and prices 212 XV. Insurance and social welfare 213 XVI. Consumption 214